2018
DOI: 10.1093/tropej/fmy033
|View full text |Cite
|
Sign up to set email alerts
|

Course of Illness after Viral Infection in Indian Children with Cystic Fibrosis

Abstract: Acute viral infection in children with CF affected course of illness on follow-up, including frequent and severe pulmonary exacerbations requiring hospitalization, intravenous antibiotics, decline in CF scores and increased mortality over next 12-18 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Our study found improved lung function in both groups at 3‐ and 6‐month follow‐up time points, but it may not be sustained in the long term due to a variety of factors including treatment adherence, intercurrent illnesses, and/or recurrent PEs 1,3 . There is also variability in the reported severity of viral‐positive PEs ranging from severe exacerbations requiring hospitalization and longer duration of intravenous antibiotic to a lower acute fall in ppFEV1 compared to viral‐negative PEs 10,11,17,22,23 . In this study, patients with viral‐positive PE had a shorter duration of hospitalization for PE compared to the viral‐negative PE group.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Our study found improved lung function in both groups at 3‐ and 6‐month follow‐up time points, but it may not be sustained in the long term due to a variety of factors including treatment adherence, intercurrent illnesses, and/or recurrent PEs 1,3 . There is also variability in the reported severity of viral‐positive PEs ranging from severe exacerbations requiring hospitalization and longer duration of intravenous antibiotic to a lower acute fall in ppFEV1 compared to viral‐negative PEs 10,11,17,22,23 . In this study, patients with viral‐positive PE had a shorter duration of hospitalization for PE compared to the viral‐negative PE group.…”
Section: Discussionmentioning
confidence: 55%
“…1,3 There is also variability in the reported severity of viralpositive PEs ranging from severe exacerbations requiring hospitalization and longer duration of intravenous antibiotic to a lower acute fall in ppFEV1 compared to viral-negative PEs. 10,11,17,22,23 In this study, patients with viral-positive PE had a shorter duration of hospitalization for PE compared to the viral-negative PE group. This finding could be attributed to the younger age and higher baseline ppFEV1 of the viral-positive PE group affecting recovery from PEs.…”
Section: T a B L E 1 Clinical Characteristics Of The Viral-positive A...mentioning
confidence: 59%
“…Viral infection in children with CF can cause pulmonary exacerbations due to direct infection, as well as secondary bacterial infection [ 9 ]. Both of the above-mentioned cases had poor respiratory health with pulmonary exacerbations after SARS-CoV-2 infection, despite having well-controlled disease in the previous year.…”
Section: Discussionmentioning
confidence: 99%
“…For people CF, the clinical relevance of respiratory viral infections was present long before the recent global COVID-19 pandemic, with clear associations between acquisition of respiratory viruses and risk of CF exacerbations [19,20] and in some cases potentially significant disease progression [21,22]. Respiratory viruses are commonly detected from samples taken at both routine and emergency CF outpatients consultations [20] and spread of influenza infection among CF inpatients, with adverse clinical morbidity following infection, has been highlighted in two recent studies [23 ▪ ,24].…”
Section: Coronavirus Disease 2019 and Other Respiratory Viral Infectionsmentioning
confidence: 99%